Perancangan dan Simulasi Mobil Bertenaga Udara Tekan dengan Matlabâ¢ Simulink - Setiawan, Andi (e-Jurnal Arus Elektro Indonesia, 2015)
In this paper, discussed the results of the development model of small car with compressed air propulsion (CAC). Modelling components of the compressed air system of the car is based on the characteristics of the existing industrial components. Model testing was carried out as a common test performed on vehicle models with alternative energy. In addition, it also presented a comparison fuel economy of a car driven by compressed air with several types of vehicles with a similar size from several manufacturers. The simulation results showed that the car with compressed air propulsion has MPGe value of 7.6, slightly higher than conventional cars in general.